Metode Dakwah Masjid Darussalam Kota Wisata dalam Memberdayakan Masyarakat Sekitar - Abdul Hamid; Rahmat Hidayat; Ali An Sun Geun (ALAMTARA, 2026)
This study aims to analyze the da'wah methods implemented by Darussalam Mosque Kota Wisata in empowering the surrounding community. This research is motivated by the important role of mosques not only as places of worship but also as centers of social development, education, and community empowerment in modern urban society. This study employed a qualitative approach using field research methods. Data were collected through observation, interviews, and documentation involving mosque administrators, Islamic preachers, social activity coordinators, and surrounding community members. The findings reveal that Darussalam Mosque Kota Wisata applies bil lisan da'wah through religious studies and spiritual guidance, bil hal da'wah through social and charitable activities, as well as educational development programs for young generations through Qur’anic learning and youth mosque activities. These da'wah methods have succeeded in increasing community participation, strengthening social relationships, and fostering social awareness among the surrounding community. This study contributes to the development of Islamic communication and broadcasting studies, particularly regarding community empowerment-based da'wah in modern mosque environments.